2020
DOI: 10.1142/s179329202050085x
|View full text |Cite
|
Sign up to set email alerts
|

Nonhazardous Electrospun Biopolymer Nanofibrous Membrane for Antibacterial Filter

Abstract: Respiratory disease caused by the presence of bacteria in the atmosphere seriously threatens human health. Air pollution as harmful suspended particles, like haze, is conducive to bacterial spread and growth; it must be prevented to avoid harming the respiratory tract. Herein, filtration membranes possessing superior antibacterial activity are considered as an effective means to protect humans from atmospheres contaminated with bacteria. The aim of this study is to prepare an environmentally friendly and biode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…[ 127 ] In the same way a high efficiency nanofibrous membrane composed of gelatin (GT) and silk fibroin (SF), in which antibacterial agent can anchor via electrostatic spinning was developed. [ 128 ]…”
Section: Esnfms Classification For Pm Filtrationmentioning
confidence: 99%
“…[ 127 ] In the same way a high efficiency nanofibrous membrane composed of gelatin (GT) and silk fibroin (SF), in which antibacterial agent can anchor via electrostatic spinning was developed. [ 128 ]…”
Section: Esnfms Classification For Pm Filtrationmentioning
confidence: 99%
“…g-C 3 N 4 conferred antibacterial ability to the composite membrane with the antibacterial efficiency of 99% under visible light irradiation for 120 min. [52] In addition, You et al [103] selected AgNO 3 as an antibacterial agent to prepare GT/Ag/SF nanofiber membranes for air filtration, and used the bacteriostatic ring method to characterize the antibacterial activity for S. aureus and E. coli. Results showed that the membrane possessed a significant antibacterial activity against S. aureus and E. coli and a water vapor transmission rate of 3781.6 g m −2 day −1 .…”
Section: Air Filtrationmentioning
confidence: 99%
“…Li et al prepared polyacrylonitrile (PAN)/polyimide (PI) nanofiber films by electrostatic spinning [15]. You et al prepared antibacterial gelatin (GT)/silk protein (SF) biopolymer nanomembranes with filtering functions by the electrostatic spinning method [16]. Although electrospinning has been studied extensively in the academic field, its low production efficiency has limited its use in industry.…”
Section: Introductionmentioning
confidence: 99%